Examining consumers' webrooming behavior: an integrated approach. Issue 3 (7th May 2019) - Arora, Sourabh; Sahney, Sangeeta
Abstract : Purpose: The purpose of this paper is to employ an integrated technology acceptance model–theory of planned behavior framework intertwined with online risk, e-distrust and product involvement to augment an understanding on consumers' webrooming behavior. Design/methodology/approach: A mix of convenience and selective sampling was used for data collection. A total of 14 propositions were put forth, which were tested using the structural equation modeling method. Findings: The results of the study revealed that apart from perceived ease of searching online and overall usefulness of the webrooming sequence, perceived search benefits online and purchase benefits offline significantly determined consumers' webrooming behavior. The results of the study also indicate that webrooming helps consumers avoid the feeling of post-purchase regret of making sub-optimal product choices offline. Online risk perceptions and e-distrust also play a notable role in inhibiting consumers' from making online purchases, and as a consequence encourage webrooming behavior. The moderating influence of product involvement was observed between consumers' intentions toward webrooming and webrooming behavior. Research limitations/implications: The research conducted provides rich insights into understanding the rising webrooming phenomenon. However, more exhaustive studies are needed to arrive at definitive findings concerning the webrooming phenomenon. Practical implications: The findings of the study can be utilized by the online retailers for formulating strategies to counter webrooming behavior. Originality/value: The paper is amongst the first few studies which contribute toward enhancing the understanding on webrooming behavior, an emerging issue in the current retailing environment.